ERBB receptors: from oncogene discovery to basic science to mechanism-based cancer therapeutics - Arteaga, Carlos L; Engelman, Jeffrey A (Cancer cell, 2014)
ERBB receptors were linked to human cancer pathogenesis approximately three decades ago. Biomedical investigators have since developed substantial understanding of the biology underlying the dependence of cancers on aberrant ERBB receptor signaling. An array of cancer-associated genetic alterations in ERBB receptors has also been identified. These findings have led to the discovery and development of mechanism-based therapies targeting ERBB receptors that have improved outcome for many cancer patients. In this Perspective, we discuss current paradigms of targeting ERBB receptors with cancer therapeutics and our understanding of mechanisms of action and resistance to these drugs. As current strategies still have limitations, we also discuss challenges and opportunities that lie ahead as basic scientists and clinical investigators work toward more breakthroughs.